1978
DOI: 10.1084/jem.147.3.800
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic responsiveness of the C3H/HeJ mouse: differential ability of butanol-extracted lipopolysaccharide (LPS) to evoke LPS-mediated effects.

Abstract: The lipopolysaccharide (LPS) 1 component of the cell wall of gram-negative bacteria possesses a broad range of biological activities and has been utilized to probe both subcellular and cellular phenomena (1-6). It is known to stimulate cell-specific activity in a diversity of cell types, including platelets (7), polymorphonuclear leukocytes (8), lymphocytes (9), fibroblasts (10), and macrophages (11) among others. Activation of lymphocytes has been studied in a number of systems: LPS has been shown to be a B-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1979
1979
1988
1988

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 47 publications
2
8
0
Order By: Relevance
“…1 B), thus demonstrating that the C3H/HeJ spleen cells were able to manifest an adjuvant response when appropriately stimulated. Our results concerning polyclonal activation by Bu-LPS and by high concentrations of Ph-LPS were in agreement with previous findings by others (9,35).…”
Section: Resultssupporting
confidence: 94%
“…1 B), thus demonstrating that the C3H/HeJ spleen cells were able to manifest an adjuvant response when appropriately stimulated. Our results concerning polyclonal activation by Bu-LPS and by high concentrations of Ph-LPS were in agreement with previous findings by others (9,35).…”
Section: Resultssupporting
confidence: 94%
“…3). This segregation of the ability to interfere with the induction of tolerance from other mechanisms of adjuvant activity has been documented previously (71) in athymic nude mice (19,20) and in the LPS-nonresponder C3H/HeJ mouse (72), with polymerized flagellin (19), LPS (20), and lipid A-associated protein (72).…”
Section: Inability Of Col Tomentioning
confidence: 97%
“…Sultzer (30) described a mutant C3H mouse, C3H/HeJ, which appeared to be resistant to the effects of phenol-extracted LPS. Further work with this strain has shown that it is refractory to virtually all LPS-mediated effects studied, including mitogenesis and PBA (7,10,34), although this strain can respond to the butanoland trichloroacetic acid-extracted LPS (10,19) which contains a low molecular weight protein bound tightly to the lipid A moiety of LPS (endotoxin protein or lipid A-associated protein ; LAP) (18,3]). We demonstrated that all of the active preparations of the cell walls and theirfractions have the ability to induce PBAeffects on cultured spleen cells of this LPS-nonresponder strain.…”
Section: Introductionmentioning
confidence: 99%